(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
This paper aimed at positioning a staff digital literacy level versus attitude toward online teaching and learning quadrant in the curriculum transformation interventions of various institutions to ensure that their policy intervention with regard to online learning remains user-friendly and sector appropriate. Using a critical autobiographical narrative inquiry, this quadrant was developed to assist educational institutions, personnel, and other stakeholders with a unique tool to assess their staff digital literacy level and the position of their attitude toward online teaching and learning. The quadrants consist of 4 sections: High Digital Literacy Level-Low Attitude Toward e-Teaching & Learning; High Digital Literacy Level-High Attitude Toward e-Teaching & Learning; Low Digital Literacy Level-Low Attitude Toward e-Teaching & Learning; Low Digital Literacy Level-High Attitude Toward e-Teaching & Learning. The quadrant used staff attitude as a yardstick to effectively implementing online learning initiatives in the education sector. The quadrants also serve as an educational re-engineering intervention strategy for the society 4.0/5.0 curriculum professionals.